2021
DOI: 10.5194/bg-18-2755-2021
|View full text |Cite
|
Sign up to set email alerts
|

Destruction and reinstatement of coastal hypoxia in the South China Sea off the Pearl River estuary

Abstract: Abstract. We examined the evolution of intermittent hypoxia off the Pearl River estuary based on three cruise legs conducted in July 2018: one during severe hypoxic conditions before the passage of a typhoon and two post-typhoon legs showing destruction of the hypoxia and its reinstatement. The lowest ever recorded regional dissolved oxygen (DO) concentration of 3.5 µmol kg−1 (∼ 0.1 mg L−1) was observed in bottom waters during leg 1, with an ∼ 660 km2 area experiencing hypoxic conditions (DO < 63 µmol kg−1)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 90 publications
1
18
0
Order By: Relevance
“…Several observational endeavors, including the cruise in this study, found that a coastal hypoxic zone still persisted despite of the passage of a TC (Su et al, 2017;Wang et al, 2017;Guo et al, 2019;Zhao et al, 2021). The time series data obtained from moorings further revealed the relief and the subsequential reoccurrence of hypoxia off the Changjiang Estuary in response to the passage of the TC (Ni et al, 2016).…”
Section: Introductionsupporting
confidence: 49%
See 1 more Smart Citation
“…Several observational endeavors, including the cruise in this study, found that a coastal hypoxic zone still persisted despite of the passage of a TC (Su et al, 2017;Wang et al, 2017;Guo et al, 2019;Zhao et al, 2021). The time series data obtained from moorings further revealed the relief and the subsequential reoccurrence of hypoxia off the Changjiang Estuary in response to the passage of the TC (Ni et al, 2016).…”
Section: Introductionsupporting
confidence: 49%
“…Wang et al (2017) suggested that apart from the strong mixing, the elevated river discharge caused by TC-induced heavy rainfall would also contribute to the nutrients needed by the subsequent phytoplankton bloom to re-establish hypoxia. Zhao et al (2021) found that although the local respiration rate was the major driver of hypoxia after passage of the TC, the invasion of subsurface water from the outer-shelf with low-oxygen content also contributed an additional 8.6 ± 1.7% of the depletion of DO in the hypoxic zone off the Pearl River Estuary. Guo et al (2019) found that although a TC eye passed through the core hypoxic zone, the stratification at the submerged river valley off the Changjiang Estuary was not completely eliminated and the residual hypoxic water persisted there.…”
Section: Introductionmentioning
confidence: 97%
“…Given the long‐term deoxygenation trend and rapid urbanization and industrialization in the PRE, bottom DO concentrations under deoxygenation in 2025 are estimated to be ∼2.0 mg L −1 and ∼1.7 mg L −1 in Southern Hong Kong and Mirs Bay, respectively, corresponding to the hypoxic criterion (2.0 mg L −1 ), which reflects that both regions probably become seasonally hypoxic. In addition, seasonal DO depletion has been observed from intermittent detection before the 2000s to consistent hypoxia covering ∼1,000 km 2 , particularly in the western part of the lower estuary by recent cruises (Qian et al., 2018; Su et al., 2017; Ye et al., 2012; Yin et al., 2004; Zhao, Uthaipan, et al., 2021). Therefore, eastern areas off the PRE adjacent to Hong Kong, not considered in most previous studies, are also vulnerable to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, more deoxygenation was observed in the bottom water of Mirs Bay, while DO supersaturation was mostly absent in the surface layer, suggesting that biological activities were weak (Zhao, Uthaipan, et al., 2021). Therefore, autochthonous organics and subsequent remineralization may not strongly explain the great decrease in DO concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Observations of THREEs are so far scarce, as their detection requires sufficient data to both constrain the HI depth variability and record the event itself. Most reports of subsurface oxygen depletion events or strong variability exist for continental shelves of eastern boundary upwelling systems (Booth et al, 2012;Chan et al, 2008;Grantham et al, 2004;Machu et al, 2019;Peterson et al, 2013), for marginal seas (Chu & Tunnicliffe, 2015;Dietze & Löptien, 2021) or for river estuaries (Eby & Crowder, 2002;Rabalais & Turner, 2019;Zhang et al, 2020;Zhao et al, 2021). In these coastal cases, the HI often shoals as a result of microbial respiration of exported organic matter while changes in mixing and circulation suppress oxygen replenishment.…”
mentioning
confidence: 99%